FOLATE AND MTHFR POLYMORPHISMS IN SLEEP, ANXIETY, AND DEPRESSION, AND VITAMIN B12 IN ANXIETY AND DEPRESSION: A REVIEW OF CURRENT EVIDENCE - Suchołbiak, Aleksandra; Mikołajczyk, Oskar; Podolak, Maja; Walkowski, Radosław Jan; Grygutis, Irmina; Jarzęcka, Urszula; Fimiarz, Kornelia Julia; Pawełkiewicz, Sonia; Łysak, Kinga (International Journal of Innovative Technologies in Social Science, 2026)
One-carbon metabolism supports neuropsychiatric function by providing the substrates needed for monoamine neurotransmitter synthesis. In this review, we summarize the available evidence on selected B vitamins and methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms in relation to sleep outcomes, depression, and anxiety in adults. A PubMed search was conducted, through which 27 studies relevant to the review were identified. Observational studies suggest that the relationship between serum folate and sleep is complex, with findings remaining inconsistent across the literature. Nevertheless, improvements in sleep disturbance outcomes following L-methylfolate supplementation among individuals with MTHFR C677T/A1298C polymorphisms provide preliminary support for a link between vitamin B9 metabolism and sleep regulation. In the context of depression and anxiety, observational studies also yielded mixed results. However, interventional studies suggest that supplementation with L-methylfolate at doses exceeding 7.5 mg/day may enhance the response to antidepressant treatment in patients with depression. Furthermore, among patients with major depressive disorder and low-normal vitamin B12 levels, adjunctive therapy with weekly intramuscular injections of 1,000 µg vitamin B12 may improve treatment response. Evidence regarding the role of MTHFR polymorphisms in anxiety and depression remains inconclusive, although some studies suggest that reduced MTHFR activity may be associated with an increased risk of these conditions and that supplementation with a reduced B vitamins and micronutrient complex may offer clinical benefit. In conclusion, vitamin B status and MTHFR polymorphisms may be related to both sleep and anxiety/depressive symptoms. However, because the current evidence remains inconsistent, further large-scale longitudinal studies and well-designed randomized controlled trials are needed.